An Overviuw Of The Teaching And Learning Process Basic Programming In Algorithm And Programming Courses - et. al., Wilda Susanti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we review the literature related to computer programming learning, where Algorithms and Programming are the topic domains of the Informatics and Computer science clusters. There are 4 competencies in learning outcomes, such as: 1) understand algorithmic concepts; 2) master algorithm concepts and principles; 3) master programming language concepts; and 4) master programming languages and algorithms. The main focus of this review is on beginner programming and topics related to student difficulties in learning programming. Various problems experienced by beginners were identified from the literature to some of the solutions offered by researchers.